Development of a Blended Learning Environment to Support Achievement of Graduate Outcomes through Optimal Learning in an Undergraduate Pharmacy Course - Alyson Brown; Helen Vosper (Pharmacy, 2013)
The development of graduate attributes through health professional courses requires the opportunity to engage with learning and teaching activities that reflect the work-based role to which the student aspires. Such activities allow the contextualisation of discipline-specific knowledge, forging a critical understanding of the underpinning theory, and providing a firm foundation for the development of lifelong learning skills. A blended learning approach can be particularly valuable in supporting achievement of the learning outcomes in modules where performance is measured in terms of competency in work-based scenarios. An action research approach was taken to develop and evaluate a cardiovascular risk assessment as the basis for clinically and professionally relevant problem-based learning. Support for this was provided by means of blended learning including a number of online activities. Talking wall focus groups were used to evaluate the student experience, and this was combined with quantitative data regarding student examination performance. Student performance in the cardiovascular section of the examination paper was significantly higher than in other sections. Students reported very favorably on the use of this approach to support not only examination preparation, but also in terms of developing professional identity and enhancing employability skills.